Lipid biomarkers and their environmental significance in mine soils from Eastern Europe. Issue 12 (15th October 2017) - Atanassova, Irena; Hristov, Biser; Shishkov, Toma; Doerr, Stefan
ABSTRACT: The present study describes signature lipid biomarkers in reclaimed mine soils (RMSs), an unreclaimed spoil and a natural soil (Vertisol) for a major coal mine basin in Eastern Europe. Alkanes, fatty acids and fatty alcohols, as well as coal biomarkers were abundant in the mine soils and the unreclaimed spoil. The alkanes distribution in the RMSs was bimodal with maxima at C18 and C29 /C31 and points at two origins for the alkanes, terrigenous plants, including soil borne and from the coal source. Fatty acid carbon preference indices (CPIeven/odd = 10.4 and 8.1 for the mine soils under pine and grass vegetation) reflect the increasing role of terrestrial vegetation in the formation of organic matter. The higher concentrations of the long-chain alkanes, fatty acids and alcohols are speculated as the reason for the severe and extreme water repellency observed with the Vertisol and the unreclaimed spoil. The presence of terrigenous steroid and triterpenoid markers in the RMSs is an indication of the ongoing soil formation processes. The analysis of lipid extracts allowed for the assessment of sensitive molecular indicators of biogenic terrigenous and coal origin and the degree of soil recovery following >20 years of spoils reclamation.